Advanced CAD/CAM Techniques for 5-Axis Machining of Free-Form Surfaces - Van Tuong, Nguyen (Manufacturing Technology Journal, 2019)
This paper presents some advanced techniques on CAD modelling and CAM programming for 5-axis machining of free-form surfaces. In the CAD stage, based on surface partitioning, the design surface can be created with separate regions such as convex, concave and saddle. Point-based techniques are used to create the original surface and the boundary curves of the regions. Some other CAD/CAM techniques for determining tool sizes and tool orientations are also proposed to generate gouge-free tool paths for each region. A simple B-spline surface was given as an example to demonstrate the proposed techniques implemented in Creo Parametric. The points on the design surface and on the boundaries were generated by a Matlab program developed by the author.
Keywords: Surface partitioning; Free-form surface; 5-axis machining; Gouge-free tool path